The Influence of Brand Equity, Brand Experience, and Brand Reputation on Brand Loyalty (Study of DANA E-Wallet Application users in Semarang City) - Pangestika, Teta Kirana; Indriani, Farida (JURNAL BISNIS STRATEGI, 2023)
The increasingly rapid development of technology has an impact on the use of e-wallet transactions. E-wallet is an innovation supported by technological developments as a digital wallet that can be accessed easily and cheaply. One e-wallet that is often used by people is DANA. This application provides many benefits to its users such as providing free transfer services and payments to various other platforms. The aim of this research is to determine the influence of brand equity, brand experience and brand reputation on brand loyalty among DANA e-wallet users. The method used in this research is a quantitative method with a sample of 100 respondents. The data analysis method used is multiple linear regression analysis. The results of this research show that brand equity has a significant influence on brand loyalty as evidenced by the calculated t value being greater than the t table (8.011>1.660). Likewise, brand experience has a significant influence on brand loyalty as evidenced by the calculated t value being greater than the t table (4.004>1.660). The influence of independent variables such as brand equity and brand experience simultaneously influences dependent variables such as brand loyalty by 73%, while 27% is influenced by factors not discussed in this research.